Poly(methyl methacrylate) particles for local drug delivery using shock wave lithotripsy: In vitro proof of concept experiment. Issue 6 (28th October 2014) - Shaked, Eliav; Shani, Yoav; Zilberman, Meital; Scheinowitz, Mickey
Abstract To leverage current local drug delivery systems methodology, there is vast use of polymeric particles serving as drug carriers to assure minimal invasive therapy with little systemic distribution of the released drug. There is an increasing interest in poly(methyl methacrylate) (PMMA) serving as carriers in drug delivery. The study aims to develop PMMA carriers for localized drug delivery and release system, combining innovative biomaterial technology and shock wave lithotripsy (SWL), and to study the effect of SWL on various concentrations of PMMA particles. We prepared PMMA particles that contain horseradish peroxidase (HRP) using a double emulsion technique, and investigated the mechanism of in vitro drug release from the carriers following exposure to SWL. We investigated the correlation between production method modifications, concentrations of the carriers subjected to SWL, and shock wave patterns. We successfully produced PMMA particles as drug carriers and stimulated the release of their contents by SWL; their polymeric shell can be shattered externally by SWL treatment, leading to release of the encapsulated drug. HRP enzyme activity was maintained following the encapsulation process and exposure to high dose of SWL pulses. Increased shock wave number results in increased shattering and greater fragmentation of PMMA particles. The results demonstrate a dose‐response release of HRP; quantitation of the encapsulated HRP from the carriers rises with the number of SWL. Moreover, increased concentration of particles subjected to the same dose of SWL results in a significant increase of the total HRP release. Our research offers novel technique and insights into new, site‐specific drug delivery and release systems. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1228–1237, 2015.